Sperm biology : an evolutionary perspective - Birkhead, Tim; Hosken, David J.; Pitnick, Scott (Elsevier/Academic Press, 2009)
This book represents the first analysis of the evolutionary significance of sperm phenotypes and derived sperm traits and the possible selection pressures responsible for sperm-egg coevolution. An understanding of sperm evolution is fast developing and promises to shed light on many topics from basic reproductive biology to the evolutionary process itself as well as the sperm proteome, the sperm genome and the quantitative genetics of sperm. The Editors have identified 15 topics of current interest and biological significance to cover all aspects of this bizarre, fascinating and important subject. It comprises the most comprehensive and up to date review of the evolution of sperm, and pointers for future research, written by experts in both sperm biology and evolutionary biology. The combination of evolution and sperm is a potent mix and this is the definitive account. * The first review survey of this emerging field * Written by experts from a broad array of disciplines from the physiological and biomedical to the ecological and evolutionary * Sheds light on the intricacies of reproduction and the coevolution of sperm, egg and reproductive behaviour.